Audiovisual Translation of English Idioms in Harry Potter and The Deathly Hallows Movie: An Analysis of English To Indonesian Subtitle - Indry Caesarria Dewi (Universitas Pendidikan Indonesia (UPI), 2016)
The research entitled Audiovisual Translation of English Idioms in Harry Potter and The Deathly Hallows Movie : An Analysis of English to Indonesian Subtitle aims at discovering types of idioms which are mostly used in the movie and analyzing the translation strategies dealing with the idioms in the movie. The data were analyzed by using a descriptive qualitative method with Fernando’s (1996) typology of idioms and Gottlieb’s (1992) strategies for the translation process of subtitling. The result of data analysis shows that pure idiom has the largest number of the total idiom found in the movie, that is 50 items (50%). The second finding shows that the most frequent strategies used by the translator is paraphrase which is used 41 times or reaches 41% of the total usage. Subsequently, strategies which less frequent in a row are transfer (40%), expansion (9%), condensation (4%), deletion (3%), and resignation (3%). By seeing the result it can be concluded that the Indonesian translator, in translating idioms in Harry Potter and The Deathly Hallows movie, tends to be source-language oriented.Keywords: Translation Strategies, Idioms, Movie Subtitle, Audiovisual Translation